Hysterical! : women in American comedy - Mizejewski, Linda; Sturtevant, Victoria, 1973- (University of Texas Press, 2017)
Amy Schumer, Samantha Bee, Mindy Kaling, Melissa McCarthy, Tig Notaro, Leslie Jones, and a host of hilarious peers are killing it nightly on American stages and screens large and small, smashing the tired stereotype that women aren't funny. But today's funny women aren't a new phenomenon-they have generations of hysterically funny foremothers. Fay Tincher's daredevil stunts, Mae West's linebacker walk, Lucille Ball's manic slapstick, Carol Burnett's athletic pratfalls, Ellen DeGeneres's tomboy pranks, Whoopi Goldberg's sly twinkle, and Tina Fey's acerbic wit all paved the way for contemporary unruly women, whose comedy upends the norms and ideals of women's bodies and behaviors. Hysterical! Women in American Comedy delivers a lively survey of women comics from the stars of the silent cinema up through the multimedia presences of Tina Fey and Lena Dunham. This anthology of original essays includes contributions by the field's leading authorities, introducing a new framework for women's comedy that analyzes the implications of hysterical laughter and hysterically funny performances. Expanding on previous studies of comedians such as Mae West, Moms Mabley, and Margaret Cho, and offering the first scholarly work on comedy pioneers Mabel Normand, Fay Tincher, and Carol Burnett, the contributors explore such topics as racial/ethnic/sexual identity, celebrity, stardom, censorship, auteurism, cuteness, and postfeminism across multiple media.